Pengaruh Keberagaman Gender, Ukuran Dewan, dan Profitabilitas Terhadap Cash Holding - Nadine Nabila Agnasta; Bambang Sutrisno (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
This study aims to analyze the effect of board of commissioner gender diversity, board size, and profitability oncash holdings in transportation and logistics companies listed on the Indonesia Stock Exchange. This research is a quantitative study by using secondary data. The population used consists of 37 companies that have beenconsistently listed on the Indonesia Stock Exchange over the past 5 years. The sampling technique employed was purposive sampling, yielding a sample of 21 companies. The method used is panel regression analysis, with dataprocessing using Stata 17 software. Model determination uses the Chow test, Hausman test, Lagrange multiplier test, hypothesis test, partial test, and coefficient of determination. The results show that board of commissioner gender diversity and board size have a positive effect but insignificant on cash holdings, while profitability shows a positive and significant effect on cash holdings. These findings imply for corporate financial managers and investors to focus not only on quantitative aspects of corporate governance but also on performance and cash management strategies to generate profits and strengthen cash positions optimally.